Tratamento de efluentes de tanques de piscicultura aplicando a tecnologia de eletrocoagulação - Silva, José Pedro Varela da (2013)
For this work, we used the technique of electrocoagulation (EC) for the treatment of effluent from fish farms. An EC reactor at laboratory scale with a capacity of 1,5 L was assembled using a set of four plates of aluminum electrodes, a mechanical stirrer high torque microprocessor, wires with alligator clips and a voltage source with power adjustable. The electrodes were arranged inside of the electrolytic cell in a monopolar form, in parallel and at a distance of 11 mm. The effluent used in this study was collected in fishponds of fish breeding center of the Engineering Department of Fisheries, Federal University of Ceará. To determine the best operating condition of the reactor, an experimental design was performed using the software "Statgrafics", defining the operational variables and their respective intervals (Initial pH 4 to 8, conductivity from 1000 to 4000 μS cm-1, electrolysis time 15 to 35 min., agitation 200-600 rpm and electrical current from 1 to 2,5 A), that combined together, performing a total of 35 runs. Based on the results obtained by means of physical-chemical analysis in the laboratory, it can be stated that the initial pH=8, conductivity=1000 μS cm-1, time=35 min., agitation=200 rpm and electrical current=2,5 A, are the optimal operating conditions of the reactor. Under these conditions, removal reached 84,95% for COD, 98,06% for nitrite, 82,43% for nitrate, 98,05% for total phosphorus and 95,32% for turbidity, resulting an operating cost of R$ 4,59 per m3 of treated effluent. Based on the results obtained, it can be concluded that some of the analyzed parameters (pH, turbidity, temperature, STD, nitrite, nitrate and total phosphorus) are in accordance with the standards established for fresh water, class 2, by CONAMA Resolution nº 357/05, and according to CONAMA Resolution nº 430/2011 and Decree nº 154/2002 of SEMACE (CE), for release of the final effluent in the receiving water bodies. The technique of electrocoagulation besides being an alternative, efficient and promising for treating effluents from fish farming, also proved to be environmentally friendly for taking the high consumption of reagents, contrary to what happens in conventional treatment.